Eating quality of the longissimus thoracis muscle in beef cattle – Contributing factors to the underlying variability and associations with performance traits. (February 2021) - Judge, M.M.; Conroy, S.; Hegarty, P.J.; Cromie, A.R.; Fanning, R.; Kelly, D.; Croften, E.; Berry, D.P.
Abstract: The objective was to determine the factors associated with meat tenderness, juiciness, flavour and chewiness in 4791 growing crossbred cattle. Meat quality of bulls was inferior to that of both steers and heifers with little difference between the latter two genders. Angus, Hereford and Belgian Blues had the most tender meat with the Simmental being the toughest albeit the difference was, on average, only 5%. Moderate to strong correlations (r ≥ |0.43|) existed among tenderness, juiciness and flavour although some of the correlations differed by animal gender. Correlations between chewiness and tenderness in the different genders varied from −0.81 to −0.74 while the correlations between chewiness and the other sensory traits varied from −0.54 to −0.09. The (partial) correlations between each of the four sensory metrics and all of carcass weight, carcass conformation and carcass fat score were ≤|0.09| with most not being different from zero. Correlations between the sensory traits with growth rate, muscle depth, feed intake and efficiency were all ≤|0.08| and mostly not different from zero. Highlights: Breed differences in tenderness were evident although the differences were biologically small. Bulls had less tender meat then heifers and steers with little difference between the latter. Meat organoleptic properties were either weakly or not correlated with a series of carcass, growth and efficiency traits.